Istanbul Strait Road Tube Crossing: Design of NATM Tunnels and Asian Transition Box Excavation. Issue 4 (August 2016) - Kohlböck, Bernhard; Koc, Onur; Ayten, Türkay
Abstract: Istanbul is among the fastest growing megacities in the world and the only one located on two continents, divided by the Bosphorus strait. The geographic situation together with the enormous growth of population impose great challenges, especially considering urban and infrastructure development. The Bosphorus Strait Road tunnel, also called Eurasia Tunnel, is the first road tunnel connecting the European and the Asian side of the city with the aim of alleviating Istanbul's traffic pressure and reducing the travel time between Kazlıçeşme and Göztepe from 100 to 15 minutes. This article focuses on the design of the twin tunnels and the transition box from NATM to TBM on the Asian side.